Dynamics Changes of Solids Gastric Emptying Post -Pancreaticoduodenectomy - Ali Ibrahim, Emad Mohammed Nabiel; El-Shazli, Mostafa A.; Kandeel, Ahmed; Nabil, Ahmed (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Gastric emptying (GE) is one of the common post-operative complications after pancreaticoduodenectomy (PD). Multiple factors have been involved in this complication. Dynamic studies such as GE scintigraphy (GES) have informed us about changes in the behavior of the stomach before and after the operation. AIM: The objective of this study is a short-term scintigraphic evaluation of GE in post-PD patients for solid food before (baseline) and after the operation for 30 days. METHODS: Between April 2016 and September 2019, 30 patients who underwent PD were investigated for the effect on GE of solids. GE scan GES was performed for the evaluation of solids in GE on pre-operative and post-operative day 30. The operative time, blood loss, the specimens’ pathology and resection margins, the interpretation of the GES study, and finally the hospital course data were all gathered and subjected to statistical analysis. RESULTS: Nineteen patients developed delayed GE (DGE) while four developed rapid GE or dumping. The type of pancreatic reconstruction affected the GE dynamics. DGE was evident in all cases with pancreaticogastrostomy (PG), while it was observed only in 4 patients of 15 with pancreaticojejunostomy (PJ). Seven cases developed a post-operative pancreatic fistula (POPF), 3 after PG versus 4 after PJ, and were all successfully managed conservatively. CONCLUSION: The reconstruction method of the remnant pancreas could affect the dynamics of GE. The DGE to solids was witnessed more in cases reconstructed by PG and less in cases with PJ. Post-operative complications associated, such as POPF, are factors associated with DGE.